A qualitative study exploring the perceived effects of veterinarians' mental health on provision of care - Campbell, Megan; Hagen, Briana N. M.; Gohar, Basem; Wichtel, Jeffrey; Jones-Bitton, Andria (Frontiers in Veterinary Science, 2023)
Veterinary medicine is a rewarding, yet demanding profession with a myriad of occupational stressors that can impact the mental health of veterinarians. Stress, mental health outcomes, and associated risk factors amongst veterinarians have been well-researched. Much less research has investigated how high stress and/or poor mental health can impact veterinarians’ provision of care. One-on-one research interviews were conducted with 25 veterinarians at a Canadian veterinary conference in July 2016 and verbatim transcripts were produced from the audio recordings. The research team collaboratively analyzed the interviews using thematic analysis. Five themes described the perceived impacts of high stress and/or poor mental health: perceived negative impacts on interactions with (1) co-workers and (2) clients; (3) reduced concentration; (4) difficulty in decision making; and (5) reduced quality of care. These results highlight the perceived impacts of self-reported high stress and/or poor mental health on veterinary team dynamics, the potential to impact case outcomes, and possibly endanger patient safety. Interventions to help mitigate the impacts of high stress and poor mental health are discussed.